Geographic altitude and prevalence of underweight, stunting and wasting in newborns with the INTERGROWTH-21st standard - Martinez, Jorge Ivan (2019)
Objective: To assess the prevalence and risks of underweight, stunting and wasting by gestational age in newborns of the Jujuy Province, Argentina at different altitude levels. Methods: Live newborns (n = 48,656)born from 2009–2014 in public facilities with a gestational age between 24+0 to 42+6 weeks. Phenotypes of underweight (2.000 m.a.s.l. Maternal age, body mass index >35 kg/m2, hypertension, congenital malformations, and prematurity were more strongly associated with underweight rather than stunting or wasting at ≥2.000 m.a.s.l. Conclusions: Underweight, stunting, and wasting risks were higher at a higher altitude, and were associated with recognized maternal and fetal conditions. The use of those three phenotypes will help prioritize preventive interventions and focus the management of fetal undernutrition.